Effect of Strawberry Extract (Fragaria x ananassa) towards Discoloration of Artificial Teeth due to Tea Immersion - Bernadetta S. D. Simamora; Brigitta N. R. Purnomo; Edward K. S. Limijadi; Nadia Hardini (e-GiGi, 2022)
Abstract: Discoloration of acrylic resin teeth can cause esthetic problem. Alkaline peroxide is commonly used as a denture cleanser, however, due to its side effects, an alternative material such as strawberry (Fragaria x ananassa) that contains ellagic acid and malic acid can be used to whiten and clean the teeth. This study was aimed to determine the effect of strawberry extract with concentrations of 65%, 75%, 85%, and 95% towards discoloration of artificial tooth due to tea immersion. This was an experimental laboratory study with a pre-test and post-test control group design. Artificial teeth made from acrylic resin were tested for color changes after immersion in tea for seven days followed by immersion in strawberry extract with concentrations of 65%, 75%, 85%, 95%, and alkaline peroxide for seven days. Color measurement was carried out using the chromameter and CIE L*a*b* system. Paired t-test showed a significant difference (p<0.05) in all values of 'L', 'a', and 'b' groups before and after treatment except for the value of 'b' immersion with alkaline peroxide and 75% strawberry extract. One way Anova test showed significant results in all groups. The strongest to the weakest tea stain cleanser was the group of 95% strawberry extract, 85% strawberry extract, alkaline peroxide, 75% strawberry extract, and 65% strawberry extract, respectively. In conclusion, strawberry extract at 65%, 75%, 85%, and 95% concen-tration affected the brightness of discolored artificial tooth due to tea immersion. The best change in brightness occurred at 95% concentration of strawberry extract.Keywords: strawberry extract; discoloration; artificial tooth; tea; alkaline peroxide Abstrak: Diskolorasi anasir gigi tiruan resin akrilik dapat menyebabkan masalah estetik. Alkalin peroksida merupakan pembersih gigi tiruan yang umum digunakan dengan beberapa efek samping sehingga diperlukan bahan alternatif seperti buah stroberi (Fragaria x ananassa) yang mengandung asam elagat (ellagic acid) dan asam malat (melic acid) yang dapat digunakan untuk memutihkan dan membersihkan gigi. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak stroberi konsentrasi 65%, 75%, 85%, dan 95% terhadap diskolorasi pada anasir gigi tiruan akibat perendaman teh. Jenis penelitian ialah eksperimental laboratoris dengan pre-test and post-test control group design. Anasir gigi tiruan berbahan resin akrilik diuji perubahan warna setelah direndam teh selama tujuh hari dan setelah direndam ekstrak stroberi dengan konsentrasi sebesar 65%, 75%, 85%, 95%, serta alkalin peroksida selama tujuh hari. Pengukuran warna dilakukan dengan menggunakan chromameter sistem CIE L*a*b*. Hasil uji paired t-test menunjukkan perbedaan bermakna (p<0,05) pada semua nilai ‘L’, ‘a’, dan ‘b’ kelompok sebelum dan sesudah perlakuan kecuali pada nilai ‘b’ perendaman dengan alkalin peroksida dan ekstrak dengan konsentrasi 75%. Hasil uji one way Anova menunjukkan hasil bermakna pada semua kelompok. Pembersihan noda teh terkuat hingga terlemah yaitu pada kelompok ekstrak stroberi 95%, ekstrak stroberi 85%, alkalin peroksida, ekstrak stroberi 75%, dan ekstrak stroberi 65% secara berturut. Simpulan penelitian ini ialah terdapat pengaruh ekstrak stroberi konsentrasi 65%, 75%, 85%, dan 95% terhadap kecerahan anasir gigi tiruan yang telah terdiskolorasi oleh teh. Perubahan kecerahan terbesar terjadi pada ekstrak stroberi konsentrasi 95%.Kata kunci: ekstrak stroberi; diskolorasi; anasir gigi tiruan; teh; alkalin peroksida